Flipped - Van Draanen, Wendelin (New York : Knopf, 2001)
In alternating chapters, two teenagers describe how their feelings about themselves, each other, and their families have changed over the years.
Keywords: Interpersonal relations -- Fiction; Conduct of life -- Fiction; Family life -- Fiction; Self-perception -- Fiction